Desenvolvimento de um sistema de redução com auto-travamento para chaves secionadoras - Palmeiro, Felipe Svonka (2015)
This study addresses the development of a torque transmission system with self-locking property to the crank drive rotate problem of the products of a company in the business of switch disconnectors. Throughout this study was sought in the literature the most cost-effective system for the company, in order to reduce the cost of the current system. The research then was directed for the pair worm and worm wheel’s self-locking property, considering that other systems with this property are unable to fulfill the needs of the project. Throughout the work the criteria for self-locking property and relations for the torque required to acquire the self-locking of the system in question were shown. And finally, have been developed over the work the methodology to design the system, the results of calculations, as well as have been evaluated these results and difficulties encountered on the conclusions of the work, which indicated that the project is feasible, given that meets the most of the requirements specified.